Latin American Democracy: what to do with the Leaders? - Tedesco, Laura (2013)
The democratic deficit, or the gap between citizens' aspirations and their level of satisfaction, is increasing in Latin America. Such dissatisfaction helps to understand many of the region's presidential crises: since 1985, 23 Latin American presidents have left government abruptly. While civil society may have been able to provoke the fall of presidents, it has not managed to avoid the re-emergence of deep-rooted political practices under subsequent administrations. Extreme presidentialism, clientelism and populism have re-emerged strengthened after deep political crises. This article offers some ideas regarding the impact that different types of political leaders can have on how well democracy works.